Pertanggungjawaban Tindak Pidana Pembunuhan yang Dilakukan oleh Anak di Polsek Mardingding - Regen Manik; Taufik Siregar; Rizkan Zulyadi (Mahesa Research Center, 2022)
The aim of this article to analysis to regulate, responsibility and how to overcome efforts to prevent children from committing murder crimes. This type of research is directed to normative juridical law research. The nature of the research is descriptive analysis, which from these results can describe (describe) thoroughly and systematically regarding the responsibility for children as perpetrators of the crime of murder.The legal arrangements for the crime of murder committed by children are: Article 338 of the Criminal Code in conjunction with Article 351 Paragraph (3) of the Criminal Code, Law of the Republic of Indonesia Number 8 of 1981 concerning Criminal Procedure Code. Law of the Republic of Indonesia Number 11 of 2012 concerning the Juvenile Criminal Justice System and Law of the Republic of Indonesia Number 35 of 2014 concerning Child Protection. The responsibility of children as perpetrators of the crime of murder is regulated in the Criminal Code and Law no. 11 of 2012 concerning the Juvenile Criminal Justice System. In the decision Number 4/Pid.Sus-Anak/2019/PN.Kbj, the child was sentenced to imprisonment for 4 (four) years. Efforts to overcome the crime of murder are carried out with penal efforts, namely by imposing criminal penalties for perpetrators and also with non-penal efforts, namely preventively, namely prevention efforts are carried out by: conducting legal counseling to the assisted villages and to schools. Conduct mobile patrols around legal areas that are prone to homicide. Placement of police officers in places suspected of being prone to crime.